Mapping the Genetic Regions Responsible for Key Phenology-Related Traits in the European Hazelnut - Valentini, Nadia; Portis, Ezio; Botta, Roberto; Acquadro, Alberto; Pavese, Vera; Cavalet Giorsa, Emile; Torello Marinoni, Daniela (Frontiers in Plant Science, 2021)
An increasing interest in the cultivation of (European) hazelnut (Corylus avellana) is driving a demand to breed cultivars adapted to non-conventional environments, particularly in the context of incipient climate change. Given that plant phenology is so strongly determined by genotype, a rational approach to support these breeding efforts will be to identify QTL (quantitative trait loci) regions and the genes underlying the basis for adaptation. The present study was designed to map QTL for phenology-related traits, such as the timing of both male and female flowering, dichogamy, and the period required for nuts to reach maturity. The analysis took advantage of an existing linkage map developed from a population of F1 progeny bred from the cross ‘Tonda Gentile delle Langhe’ x ‘Merveille de Bollwiller’. A total of 42 QTL-harboring regions were identified. Overall 71 QTL were detected; among these, 21 were classified as major. A search of the key genomic regions revealed 22 candidate genes underlying the set of traits being investigated.